Furin-instructed aggregated gold nanoparticles for re-educating tumor associated macrophages and overcoming breast cancer chemoresistance. (August 2021) - Xie, Rou; Ruan, Shaobo; Liu, Jiaqi; Qin, Lin; Yang, Chuanyao; Tong, Fan; Lei, Ting; Shevtsov, Maxim; Gao, Huile; Qin, Yi
Abstract: Insufficient drug accumulation and chemoresistance remain two major challenges in cancer chemotherapy. Herein, we designed a furin-responsive aggregated nanoplatform loaded with doxorubicin (DOX) and hydroxychloroquine (HCQ) (AuNPs-D&H-R&C) to combine chemotherapy, autophagy inhibition and macrophage polarization. AuNPs-D&H-R&C could passively target breast tumor via enhanced permeability and retention (EPR) effect after systemic administration and further aggregate together triggered by furin overexpressed in breast cancer. The in situ aggregations hindered the back-flow of NPs to the bloodstream and exocytosis of tumor cells, leading to enhanced drug accumulation within tumors. Moreover, upon exposure to acidic pH in the endosomes/lysosomes, HCQ was efficiently released and it inhibited autophagy and thus restored the sensitivity of tumor cell to DOX. Meanwhile, autophagy inhibition could reprogram tumor-promoting M2-like TAMs to anti-tumor M1 phenotype, exerting a synergistic effect in overcoming chemoresistance. In vitro studies demonstrated the superiority of furin-triggered aggregated AuNPs delivery system in enhancing drug accumulation in breast tumor, compared with PEGlyated AuNPs. The co-delivery of DOX and HCQ showed much improved chemotherapeutic efficiency to chemoresistant MCF-7/ADR breast tumor, in large part due to macrophage polarization. In conclusion, we developed a stimulus-responsive delivery system and proposed a potential combination strategy to overcome chemoresistance in cancer chemotherapy. Graphical abstract: Image 1